GAMBARAN PENGETAHUAN DAN SIKAP IBUTENTANG IMUNISASI POLIO - Margareta Rinjani; Ellen Rosdiana Pardede; Pradila Jatiningtyas (Jurnal Ilmu Kebidanan, 2018)
Imunisasi merupakan pemberian kekebalan tubuh terhadap suatu penyakit dengan memasukkan sesuatu kedalam tubuh agar tahan terhadap penyakit yang sedang mewabah atau berbahaya bagi seseorang. Untuk mengetahu iGambaran Pengetahuan Dan Sikap Ibu Tentang Imunisasi Polio.Penelitian ini bersifat deskriftif, dengan pendekatan cross sectional, Teknik pengambilan sampel dalam populasi ini dengan menggunakan teknik accidental sampling... Diperoleh hasil analisis sebagian besar responden memiliki pengetahuan baik yaitu sebanyak 15 responden (16,5%) dari 91 responden. Mayoritasresponden yang memiliki sikap positif sebanyak 53 responden (58,24%) dan minoritassikap negatif sebanyak 38 responden (41,75%) tentangImunisasi Polio Di Klinik Maria Suroso. Immunization is an immune administration of the disease by inserting something into the body to withstand the disease that is being made up or harmful to a person. Immunization administration is one of the important actions that must be given to neonates. To know the knowledge overview and attitude of the mother about Polio immunization.The study is deskriftif, with a cross sectional approach, sampling techniques in this population using accidental sampling techniques. The population referred to in this study is that all mothers who have babies who come to visit at Maria Suroso Clinic amounted to 906 people. A picture of knowledge and attitude of mother about Polio immunization at Maria Suroso Clinic in Bandar Lampung year 2017 against 91 respondents. Obtained by the analysis of most of the respondents have a good knowledge of 15 respondents (16.5%) of 91 respondents. The majority of respondents who have a positive attitude of 53 respondents (58.24%) and minority negative attitudes as much as 38 respondents (41.75%) About Polio Immunization at Maria Suroso Clinic.